2012
DOI: 10.1299/jtst.7.603
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Turbulence Promoters of Gas Turbine Blades on Film Cooling Performance

Abstract: The effects of orientation of turbulence promoting ribs in the internal cooling air passage on the film cooling performance of outer surface of gas turbine blades have been studied experimentally. Both the adiabatic film cooling effectiveness and the heat transfer coefficient downstream of the film-cooling hole of a flat plate were measured for two different orientations of the turbulence promoting ribs. It is found that the adiabatic film cooling effectiveness and heat transfer coefficient on the external sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 19 publications
(18 reference statements)
0
22
0
Order By: Relevance
“…More recently, the effect of turbulence promoting ribs for internal convective cooling has been considered by Kissel et al (5) . The authors of the present paper have experimentally shown that the rib orientation has a marked effect on the film-cooling performance evaluated in terms of the net heat flux reduction (hereafter, γ) and the net surface temperature reduction (hereafter, χ) (6) . In their subsequent study (7) , the mechanisms underlying the modifications of the adiabatic film cooling effectiveness (hereafter, η) due to rib orientation have been shown from the results obtained from computational fluid dynamics (CFD) analysis.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…More recently, the effect of turbulence promoting ribs for internal convective cooling has been considered by Kissel et al (5) . The authors of the present paper have experimentally shown that the rib orientation has a marked effect on the film-cooling performance evaluated in terms of the net heat flux reduction (hereafter, γ) and the net surface temperature reduction (hereafter, χ) (6) . In their subsequent study (7) , the mechanisms underlying the modifications of the adiabatic film cooling effectiveness (hereafter, η) due to rib orientation have been shown from the results obtained from computational fluid dynamics (CFD) analysis.…”
Section: Introductionmentioning
confidence: 80%
“…1. This configuration is the same as the film-cooling configuration examined in our previous experimental (6) and numerical (7) studies. The domain considered here includes heat transfer surfaces, an internal passage and a film-cooling hole, representing an enlarged simplified model of the real turbine blade.…”
Section: Geometries and Conditionsmentioning
confidence: 99%
See 3 more Smart Citations